Immersion Cooling and Heatsink System Using Mineral Oil for Enhancing Efficiency and Performance of Polycrystalline and Monocrystalline Solar Panels - Suseno T, Moch Adjie; Taqwa, Ahmad; RS, Carlos (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
Utilizing solar energy is essential for solving the world's energy and environmental problems, however efficiency concerns brought on by solar panels' high temperatures make it difficult. This study looks into alternative cooling techniques that use heatsinks and mineral oil instead of water as in earlier research. Mineral oil, which is frequently utilized in data center cooling systems, efficiently dissipates heat without producing the noise that conventional fans do. According to the findings, polycrystalline panels equipped with immersion and heatsink cooling outperform panels without cooling by 3.57% in power output and 3.28% in efficiency. They also perform 1.80% and 1.42% better, respectively, than panels that merely have heatsinks. Comparing monocrystalline panels to uncooled panels, they perform better, producing 4.46% more power and 4.63% more efficiently. They also outperform panels that merely have heatsinks by 3.33% and 3.08%. By lowering surface temperatures, these cooling methods have the potential to greatly increase the efficiency of solar panels. However, as the data was gathered during 15 sessions between December 2023 and May 2024, more thorough investigation is required for a thorough comprehension. Longer testing is also required for more dependable results.